Manifestações de imigrantes venezuelanos de 4º e 5º anos do ensino fundamental no contexto de práticas associadas ao ensino e à aprendizagem matemática - Oliveira, Gabrielli Monteiro de (2024)
Considering the significant number of immigrants who have arrived in Brazil recently and that many of these immigrants are enrolled in the country's education systems, we understand the necessity of conducting studies on the inclusion of immigrants in Brazilian schooling, specifically Venezuelan immigrants who, according to the 2020 school census, constitute the largest number of immigrant children enrolled in the Brazilian education network. Based on Ole Skovsmose, including studies on different types of inclusion, this work addresses the inclusion of students with different cultural backgrounds in the same educational context. The master's research currently being developed aims to investigate practices associated with the teaching and learning of mathematics that Venezuelan immigrant students experience in Brazilian and Venezuelan schooling. For data collection, we used discussion groups, group activities, and individual interviews conducted in weekly meetings with Venezuelan immigrant students enrolled in the 4th or 5th grades of Elementary School in a municipal educational institution in Cascavel and who have attended at least one year of schooling in their country of origin. The meetings were recorded in audio or video. It was decided to address the operations of addition, subtraction, multiplication, and division through questions, mathematical games, or activities involving these operations, in order to gather clues and understand the reality of math teaching and learning experienced by students in both countries: Venezuela and Brazil. For the data organization process, we used the ATLAS.ti software and for analysis, we used qualitative content analysis (Mayring, 2002). The results show that students in Venezuela also learned to solve operations through algorithmic processes, just as in Brazil. Regarding division, they are taught in Venezuela to use the usual algorithm through the short process, whereas in Brazil they are being taught through the long process. The data indicated that Venezuelan schools lack resources and pedagogical materials for teachers to work with, which hinders teaching practices, and that there are teachers without adequate training, especially after the pandemic, due to qualified teachers leaving the country because of socio-economic and political crises. In Brazil, students indicated that they feel discriminated against for not understanding the Portuguese language and are treated with indifference by some teachers.